A Multivariate Filter for Measuring Potential Output and the NAIRU Application to the Czech Republic - Benes, Jaromir (IMF Working Papers; Working Paper ;, 2004)
This paper presents a multivariate (MV) methodology for obtaining measures of excess demand that can facilitate discussion of monetary policy issues and improve policy decisions. Using data for the Czech Republic, a growing economy undergoing major structural change, it shows how the use of more information to condition the paths of potential output and the non accelerating inflation rate of unemployment (NAIRU) improves on univariate methods as the Hodrick-Prescott (HP) filter.